Penta Helix in Realizing the Capacity for Social Innovation Development in Addressing Coastal Poverty - As’ari Hasim; Adianto Adianto; Hadi Ahmad; Adhayanto Oksep; Rahmawati Nanik; Nazaki Nazaki; Vani Resa Vio (E3S Web of Conferences)
This study analyzes the role of the Penta Helix in developing social innovation to address poverty in the coastal areas of the Riau Islands. Using a qualitative research method with a case study approach, problem mapping and previous studies were conducted using VOS Viewer. Data collection techniques included observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation, while the analysis used the Miles and Huberman method. The results show that high poverty rates in several coastal areas, such as Lingga Regency and Tanjung Pinang City, have led to social problems such as crime, social instability, and migration. Limited access to education, healthcare, and employment opportunities worsens the situation. Although empowerment programs have been implemented, their results remain limited. A collaborative innovation approach involving various stakeholders through the Penta Helix proves to be effective in creating more sustainable solutions to empower coastal communities. Cross-sector collaboration between the government, private sector, academia, and local communities is expected to improve welfare and reduce the impact of social disasters caused by poverty.